Abnormal coronary vascular response in patients with long COVID syndrome: a case‐control study using oxygenation‐sensitive cardiovascular magnetic resonance - Weberling, Lukas D.; Hillier, Elizabeth; Friedrich, Matthias G.; Zahlten, Marc; Frey, Norbert; André, Florian; Steen, Henning (Journal of cardiovascular magnetic resonance, 2025)
Background - Following the worldwide coronavirus disease 2019 (COVID-19) pandemic, many patients reported ongoing severe cardiovascular symptoms after the acute phase. This multisystemic condition has been named long COVID syndrome. While cardiovascular magnetic resonance (CMR) imaging is the gold standard to diagnose acute myocardial damage, no specific changes have been shown in long COVID patients. However, endothelial dysfunction has been hypothesized to contribute to its pathogenesis. Oxygenation-sensitive CMR during breathing exercise is a simple, non-invasive, and accurate test to objectify vascular function, which has not been applied to long COVID patients yet. - Methods - After receiving approval from the local ethics committee, this prospective observational case-control study enrolled (i) patients reporting symptoms for ≥6 weeks following an acute COVID-19 infection or vaccination, and (ii) healthy volunteers with neither symptoms nor history of cardiovascular disease. Participants completed a questionnaire, point-of-care testing of cardiac biomarkers, a standard non-contrast CMR, and an oxygenation-sensitive CMR. Heart rate response and breathing-induced myocardial oxygenation reserve (B-MORE) were assessed during metronome-paced hyperventilation and apnea. - Results - Thirty-one patients (17 female; age 39.4 [30.3; 51.6] years) and 27 controls (12 female; age 33.3 [27.3; 46.8] years) were included with comparable demographics and cardiovascular risk factors between groups. Laboratory testing and standard CMR did not reveal any pathologies in either of the groups. Indexed left ventricular stroke volume was significantly lower in patients (44.5 mL [41.2; 46.6] vs 55.9 mL [49.2; 59.2]; p < 0.001), while ejection fraction and longitudinal strain of both ventricles were comparable (p > 0.05 for all). Vasoactive breathing exercises induced a significant increase in heart rate (+35/min [21; 45]) and B-MORE (9.8% [4.3; 17.2]) in controls. In patients, however, heart rate increase was blunted (+15/min [7; 26]; p < 0.001) and B-MORE was significantly lower (7.3% [3.4; 10.4], p = 0.044). - Conclusion - This pilot study is the first to show a blunted hemodynamic and myocardial oxygenation response to vasoactive breathing maneuvers during oxygenation-sensitive CMR in long COVID patients. This simple, non-invasive test may be the first to objectify complaints of affected patients and indicates evidence for the crucial role of the endothelium in the pathophysiology of long COVID.